Linguistic Aspects of «Unnatural» Narratology: The Image of a Non-existent Text Author - Бацевич, Флорій Сергійович (Київський національний університет імені Тараса Шевченка, 2019)
The article tries to implement the methods of the so-called «unnatural» narratology to analyse the texts of the collection of short stories «Absolute Emptiness» («Doskonała prόżnia»), which is a set of reviews on non-existent texts. In story-telling structures of this kind, an author usually forms and a reader usually cognitively processes: (a) new types of these structures (schemes), which are not generated in non-estranged texts; (b) new narrative strategies, in particular, the reference part of the textual story may contain actors impossible to be met in «usual» texts; (c) narrative approaches to the formation and evaluation of story-telling structures where there are objects, persons, etc. absent in the real life; (d) means of «restoring» the images of the non-existent authors in the «body» of other texts (in particular, paratexts similar to reviews). The article proves that literary narratives that reflect the non-existent texts demand additional cognitive efforts from an addressee to perceive the communicative senses generated in them. The most important source of such senses creation is a specific logic of the world perception and its reflection, which is non-characteristic to the «classical» speech genre of a review. In view of linguistic pragmatics, these texts actualize special points of view, empathy, and means of their focus. The author’s standpoint about the non-existent text and its reconstruction in paratexts form a shifted focus of empathy, and, what is more, generate non-usual communicative senses, the perception of which demands additional cognitive and psychological efforts from the addressee (a reader, a listener).

У статті на матеріалі збірки оповідань відомого польського письменника-фантаста Станіслава Лема «Абсолютна порожнеча» («Doskonała prόżnia»), яка являє собою рецензії на неіснуючі тексти, апробуються прийоми аналізу в межах так званої «неприродної» наратології. У подібних оповідних структурах автором формуються, а адресатом когнітивно опрацьовуються: (а) нові типи таких структур (схем), які не породжуються в неодивнених текстах; (б) нові наративні стратегії, зокрема, референтна частина текстової історії може містити акторів, неможливих у «нормальних» текстах; (в) наративні підходи до формування й оцінки оповідних структур, в яких наявні неіснуючі в реальності об’єкти, особи і т. ін.; (г) способи «відтворення» образів неіснуючих авторів неіснуючих текстів в «тілі» інших текстів (зокрема паратекстів на зразок рецензій). Доведено, що художні наративи, в яких відтворюються неіснуючі тексти, вимагають від адресата додаткових когнітивних зусиль осмислення породжуваних у них комунікативних смислів. Найважливішим джерелом утілення таких смислів стає особлива логіка сприйняття і представлення світу, нехарактерна, наприклад, для «класичного» мовленнєвого жанру рецензії. З позицій лінгвістичної прагматики в таких текстах втілюється особливі точки зору, емпатії, способи їхнього фокусування. Точка зору автора щодо неіснуючого тексту, його реконструкція в паратекстах формує зміщений фокус емпатії, а найголовніше – породжує неузуальні комунікативні смисли, сприйняття яких потребує від адресата (читача, слухача) додаткових когнітивних і психологічних зусиль.
Лінгвістичні аспекти «неприродної» наратології: образ автора неіснуючого тексту
Keywords: narratology; «unnatural» narratology; narrative structure; communicative sense; наратологія; «неприродна» наратологія; наративна структура; комунікативний смисл